Domestic and trade policies affecting the world cotton market - Traoré, Fousseini (International Food Policy Research Institute, 2017)
While not a food item in and of itself, cotton is important for food security in many developing countries. The cotton sector is also subject to a lot of controversy regarding its role in development, poverty alleviation, North–South trade, and environmental destruction (Mancini et al. 2005); the crop has been successively depicted as increasing or decreasing poverty and as worsening countries’ public deficits because of mismanagagement (Moseley and Gray 2008). Yet a closer look at the topic shows that cotton is a major source of cash income for millions of people, particularly in Africa, where it is also a source of foreign exchange earnings for more than 15 countries (Tschirley, Poulton, and Labaste 2009). For example, in Mali (a least developed country, or LDC) three million people make their livelihoods directly off cotton production (Sanogo, Keita, and Sanogo 2009). In addition to providing producers with cash income, cotton also appears to be a key product for fighting rural poverty and achieving food security for several other reasons.